Dry joint stone masonry walls subjected to in-plane combined loading - Lourenço, Paulo B. (2005)
The paper presents the results of experimental research on the structural behavior of dry joint masonry. The most relevant experimental results concern the strength response of stone dry joint masonry walls subjected to in-plane combined compressive and shear loading. Significant features of the structural behavior shown by the walls are discussed and conclusions on their ultimate capacity and observed failure mechanisms are addressed. Complementarily, the application of an existing numerical model, stemming from plasticity and based on a micromodeling strategy, is also presented and discussed with regard to its capacity to simulate the obtained experimental results. The model was calibrated with data collected from complementary tests carried out on specimens and prisms made of the same type of stone. Finally, the usage of a simplified method of analysis based on a continuum of diagonal struts is also addressed.